Environmental Ethics in The Novel Pertarungan by Hanna Rambe and The Novel Ping! A Message from Borneo by Riawani Elyta and Shabrina W.S: Ecocritic Studies - Busairi, M.; Supratno, Haris; Tjahyono, Tengsoe (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to describe environmental ethics in the novel Pertarungan by Hanna Rambe and the novel Ping! A Message from Borneo by Riawani Elyta and Shabrina W.S through ecocritic studies. The focus of this research includes, (1) anthropocentrism, (2) biocentrism, (3) ecocentrism in Hanna Rambe Pertarungan novel and Ping! A Message from Borneo by Riawani Elyta and Shabrina W.S.The research theory used is ecocritic to describe research data related to environmental ethics. This study uses a qualitative approach. The research data sources are the novel Pertarungan by Hanna Rambe and the novel Ping! A Message from Borneo by Riawani Elyta and Shabrina W.S. Research data are direct or indirect quotations and speeches or dialogues related to the research focus. Data collection techniques are carried out by determining literary works, critical reading, marking pages, and storing the corpus of data. The data analysis technique used hermeneutic technique. Checking the validity of the data is done by triangulation and peer discussion.The research findings are as follows. (1) Anthropocentrism in the novel Pertarungan by Hanna Rambe and Ping! A Message from Borneo by Riawani Elyta and Shabrina W.S, is shown by the attitude of the characters who do (a) hunt animals, (b) destroy forests, and (c) damage the environment. (2) Biocentrism in the novel Pertarungan by Hanna Rambe and Ping! A Message from Borneo by Riawani Elyta and Shabrina W.S, is shown by the attitude of the character who has (a) an attitude of love and care, (b) an attitude of responsibility, (c) an attitude of respect for nature. (3) Ecocentrism in the novel Pertarungan by Hanna Rambe and Ping! A Message from Borneo by Riawani Elyta and Shabrina W.S, is shown by the character's attitude in making efforts to (a) save the environment, and (b) save animals. The results of this study also show that the novel Pertarungan by Hanna Rambe and the novel Ping! A Message from Borneo by Riawani Elyta and Shabrina W.S is a green literary genre novel as an effort to convey concern for the natural environment and can be a reference for learning text analysis in Indonesian language and literature subjects.